Call me maybe: experimental evidence on using mobile phones to survey microenterprises - Garlick, R; Orkin, S; Quinn, S (Oxford University Press, 2019)
We study the effect of differences in survey frequency and medium on microenterprise survey data. We randomly assign enterprises to monthly in-person, weekly in-person, or weekly phone surveys for a 12-week panel. We find few differences across groups in measured means, distributions, or deviations of measured data from an objective data quality standard provided by Benford’s Law. However, phone interviews generate higher within-enterprise variation through time in several variables and may be more sensitive to social desirability bias. Higher- frequency interviews do not lead to persistent changes in reporting or increase permanent attrition from the panel but do increase the share of missed interviews. These findings show that collecting high frequency survey data by phone does not substantially data quality. However, researchers who are particularly interested in within-enterprise dynamics should exercise caution when choosing survey medium.